2017
DOI: 10.1097/md.0000000000007797
|View full text |Cite
|
Sign up to set email alerts
|

Immediate breast reconstruction with omental flap for luminal breast cancer patients

Abstract: Rationale:Luminal subtype breast cancer, accounting for 70 to 80% of all breast cancers, has been reported to be associated with good prognosis. However, for the patients with large mass or worse mass position, omental flap transplantation may provide a new option for breast reconstruction.Patient concerns:Ten patients (6 luminal B1, 2 luminal B2, 2 luminal A), were enrolled into the study, between January 23, 2015 and August 22, 2016. The mean age was 34.6 ± 6.96 (24-44) years old. Immunohistochemistry demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Specifically, 83.9% of the identified cases (339/404) were evaluated as satisfactory, excellent or good, which indicates satisfactory bilateral symmetry (Table 4 ). The main reasons for unsatisfactory cosmetic results included intraoperative flap necrosis, partial flap loss during convalescence and volume insufficiency 6 , 15 , 16 . Moreover, several articles reported that the omentum could be very firm after surgery 3 , which was also observed in this study, and there were temporary slight deformities after postoperative irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, 83.9% of the identified cases (339/404) were evaluated as satisfactory, excellent or good, which indicates satisfactory bilateral symmetry (Table 4 ). The main reasons for unsatisfactory cosmetic results included intraoperative flap necrosis, partial flap loss during convalescence and volume insufficiency 6 , 15 , 16 . Moreover, several articles reported that the omentum could be very firm after surgery 3 , which was also observed in this study, and there were temporary slight deformities after postoperative irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a free omental flap can reach the medial quadrant through a tunnel in the retro-mammary space with several stitches for fixation on the surrounding gland; furthermore, a free omental flap can repair axillary tissue defects very well after ALND (Figure S2 ). Our systematic review showed that the thoracodorsal vessel, rather than the inner mammary vessel, was usually the first choice of donor vessel 3 , 10 , 15 , 16 , since it is more familiar to the breast surgeon and easier to expose. Compared with the deep internal thoracic artery and thoracoacromial artery, the thoracic dorsal artery has a secluded location, stable anatomy, and similar diameter to the right artery of the stomach omentum, making it the usual first choice for us to perform anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional breast conserving therapy (BCT) uses a transferred muscle flap for breast reconstruction, which not only causes large trauma, but also complications such as muscle atrophy, thus affecting the appearance of the breast (16). Some scholars put forward that omentum with similar touch feel to breast could be applied for breast filling in that omentum is rich in blood supply and can reduce the chance of skin flap necrosis, becoming the most suitable materials (17,18). In radical mastectomy, the removal of unilateral subcutaneous mammary gland and the filling of residual cavity with pedicled omentum can reconstruct the breast that is similar to the original one (19).…”
Section: Discussionmentioning
confidence: 99%
“…The inframammary fold and lateral radian of the breast were manually adjusted to make the lateral radian as plump as possible, and smooth blood supply to the nipple was observed. 10 …”
Section: Methodsmentioning
confidence: 99%
“…The inframammary fold and lateral radian of the breast were manually adjusted to make the lateral radian as plump as possible, and smooth blood supply to the nipple was observed. 10 The axillary drainage was positioned at the point where the midaxillary line met the nipple level. The drainage tube of reconstructed breast residual cavity was placed in the greater omentum and subcutaneous space, the position…”
Section: Breast Reconstructionmentioning
confidence: 99%